Incapacidade Auto-Reportada e Retorno à Actividade Profissional - Serpa, Rui (2011)
Work-absenteeism due to the condition of Low Back Pain (LBP) presents itself as a public health problem with high economic costs in Western societies. Objective: The aim of this study was to assess the ability to return to work on patients with chronic LBP, and examine the relationship with the levels of self-reported disability. Secondly we intend to evaluate the influence of fear-avoidance beliefs to the levels of self-reported disability. Methods: We conducted a prospective cross-sectional study in which we observed 42 patients chronic LBP with new episodes of exacerbation of their symptoms. After a 3 months follow-up we evaluated the return to work in and its relationship with initial levels of disability according whit the classification system developed by Dionne et al. (2007). Results: There was a negative correlation between levels of disability and “return to work in good health” success (ρ = -0.369, p = 0.016), with the highest scores correspond to the failure in the work-return. We also found a positive correlation between the existence of fear-avoidance beliefs for work and disability (r = 0.511; p = 0.001), with a predictive value of these fear-avoidance beliefs (β = 0.533; p = 0.001) in selfreported disability. Conclusions: The ability to return to work in chronic LBP patients, after a new episode of exacerbation of symptoms is related to the levels of functional disability. Psychosocial factors, including fear-avoidance beliefs for work showed a predictive value for the self-reported disability.